Features of draws of corner kicks in games of teams of high qualification - Andrii Pertsukhov; Andrii Pertsukhov (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to define quantity and efficiency of corner kicks in games of teams-participants of the World Championship of 2014. Material &Methods: analysis of scientific and methodical literature, registration of technical and tactical actions, methods of mathematical statistics. The research of the competitive activity was carried out with teams-participants of the World Championship of 2014. Results: quantitative and quality indicators of draws of corner kicks in games of teams of high qualification are presented. Conclusions: teams-participants of the World Cup of 2014 carried out 5,2 corner kicks. The efficiency of draw of corner kicks made 44,5% on average for a game.